Possibility of Using the Embryo Fetoplacental Complex Products to Correct Apoptotic Processes under Autoimmune Diseases - Goltsev, A. N.; Grischenko, V. I.; Rassokha, I. V.; Ostankov, M. V. (Problems of Cryobiology and Cryomedicine, 2003)
The authors have studied the activity of immune competent cells in an experimental model of rheumatoid arthritis in mice. There was demonstrated the possibility to apply the products of embryo fetoplacental complex (PEFPC) to modulate the apoptotic processes under autoimmune diseases (AIDs). Â 